Molekuljarno-geneticheskie tehnologii v sporte vysshih dostizhenij - Mosset, I. (Science in Olympic Sport, 2019)
Objective. Analysis of the validity of the use, opportunities and information content of molecular genetic technologies in sport. Methods. Data analysis of modern scientific and methodical literature, sports press, Internet. Results. A review article deals with the analysis of sports genetics formation and development. According to modern concepts, various qualities are necessary for different sports events, for instance, endurance or the ability to short-term "explosive" efforts. In accordance with the discovered effects of gene polymorphisms, alleles are identified that are associated with the development and manifestation of endurance or speed and strength, or any other physical qualities. Various areas of this field of genetics are described - development of programs for selecting young athletes, genetic testing of elite athletes, determination of the expression of sports success genes, identification of the genetic risk of professional diseases and injuries in athletes and development of methods for detecting gene doping. At the present stage, scientists have come to the conclusion that it is enough to test 11-15 main "sports" genes that significantly affect the performance of an athlete. Genetic testing of elite athletes allows to identify unfavorable gene variants to correct their effects in some athletes and to detect rare alleles favorable for the development of novice athlete selection programs, the presence of which provides advantages in various sports events.A number of results obtained during molecular genetic testing of athletes specialized in various sports events are presented. It is demonstrated that the frequencies of positive variants for most genes among elite athletes significantly exceed the average values peculiar for the population as a whole, which means that these athletes have a good genetic component necessary to achieve high sports results. Conclusion. The above areas of sports genetics are necessary to provide each athlete with the conditions for the full realization of his genetic potential. Therefore, each athlete must have a genetic passport, which should indicate the options for the genes necessary to achieve high sports results in the selected sports event, the levels of these gene expressions at rest and during exercise, as well as risk genes for professional pathologies.